LAND TENURE SECURITY ISSUES IN SMALLHOLDER IRRIGATION SCHEMES IN ZIMBABWE - Mutambara, Solomon; Darkoh, Michael B.K.; Atlhopheng, Julius R. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The main objective of the study was to examine land tenure practices and their implications on the sustainability of the smallholder irrigation schemes in Zimbabwe. The different phases of land reforms in Zimbabwe have not been focusing on community irrigation schemes and the evolution of land rights. The farmers ownership feelings were stronger for their dryland plots than they were on irrigation plots as the irrigation schemes were regarded as an off-farm employment while their dry-land plots were regarded as transgenerational family assets. Farmers had different perceptions about the security of tenure, inheritability, subletting and disposal of the irrigation plots. The differences in tenure practices and perception attested to the absence of land policy for community irrigation schemes. The existence of informal land markets in some schemes and their absence in others affirmed the Market for the Poor (M4P) assertion that where formal rules and their application are weak, the business environment is governed by the informal rules and the absence of both formalrules and informal institutions make the environment for markets dysfunctional. Some farmers felt theirrigation plots should remain state owned to allow smooth running of schemes and management of farmers group dynamics of the irrigation. Some, however, felt the irrigation plots should be privately owned in order to allow farmers to invest and to access financial and input markets.